Studies on a sap transmissible virus associated with mosaic disease of cowpea - K.V. KESHAVA MURTHY, N. NAGARAJU and (Indian Phytopathology, 2002)
A mosaic disease of cowpea Vigna unguiculata (L.) Walp. characterised by systemic mosaic with dark and light green patches on the fully expanded leaves and dark green vein-banding was investigated. The causal virus was found to be transmissible by sap, seed and two species of aphids viz., Aphis craccivora and Myrus persicae. The virus had a dilution end point of I: 1000 - I :5000, thermal inactivation point between 60°- 65°C and longevity in vitro of 24 to 48 hr at room temperature (23°-25°C) and 7 days (165 hr) at refrigerated temperature (14°C). The host range of the virus was restricted to 9 only out of 41 hosts tested. The virus produced chlorotic spot and thickening along veins in Cucurbita moschata and Luffa acutangula, systemic mosaic in Cajanus cajan, Cyamopsis tetragonaloba, Phaseolus aureus and Phaseolus vulgaris, chlorotic local lesions on Chenopdoium amaranticolor and C. quinoa and systemic necrosis on Dolichos biflorus . The virus was identified as a cowpea strain of cucumber mosaic virus (CMV).